2021
DOI: 10.3390/ijerph18157735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Power and Ballistic Training on Table Tennis Players’ Electromyography Changes

Abstract: The aim of the present study was to analyze the effects of ballistic and power training on table tennis players’ electromyography (EMG) changes. Thirty male table tennis players, who were able to perform top spin strikes properly, were randomly assigned to three groups: power training (PT; n = 10); ballistic training (BT; n = 10); and no training (CON = control group; n = 10). PT and BT were performed 3 times weekly for 8 weeks. Before and after training programs, a one-repetition maximum test (1RM) and the EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…The size of the plotted squares reflects the statistical weight of the study. EG, experimental group Albayati & Kaya (2022) , Behringer et al (2013) , Haghighi et al (2021) , Kaabi, Mabrouk & Passelergue (2022) , Salonikidis & Zafeiridis (2008) , Zaferanieh et al (2021) .…”
Section: Resultsmentioning
confidence: 99%
“…The size of the plotted squares reflects the statistical weight of the study. EG, experimental group Albayati & Kaya (2022) , Behringer et al (2013) , Haghighi et al (2021) , Kaabi, Mabrouk & Passelergue (2022) , Salonikidis & Zafeiridis (2008) , Zaferanieh et al (2021) .…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies [ 26 , 40 , 83 , 85 , 98 , 99 , 103 , 105 , 107 , 108 ] examined non-athletes (including resistance-trained participants and physical education students). Other studies examined athletes from different sports such as handball (n = 5) [ 86 , 88 , 90 , 91 , 96 ], basketball [ 28 , 82 , 101 ], baseball [ 41 , 89 , 104 ], tennis [ 93 , 94 , 110 ], volleyball [ 20 , 21 , 106 ] (n = 3 for each sport), cricket [ 84 , 102 ] (n = 2), golf [ 87 ], karate [ 97 ], rugby [ 100 ], softball [ 92 ], and table tennis [ 95 ] (n = 1 for each sport). Of note, one study [ 109 ] included participants from different sports (i.e., water polo, field hockey, gymnastics, and volleyball).…”
Section: Resultsmentioning
confidence: 99%
“…speed and explosive force), speed and accuracy of the serve, and speed of response to returning the serve for the tennis player. The sample included (10) players from the youth category under the age of 20 who represent the entire research community of players affiliated with the Central Iraqi Tennis Federation in Baghdad. The researcher concluded by the study indicated that the proposed exercises have brought about a noticeable development in the speed of response.…”
mentioning
confidence: 99%